The Gambia : Fourth Review under the Extended Credit Facility Arrangement, Request for a Waiver of Nonobservance and Modification of a Performance Criterion, and Financing Assurances Review - Press Release; Staff Report; and Statement by the Executive Director for The Gambia. - International Monetary Fund. African Dept.. (Washington, D.C. : International Monetary Fund, 2022)
The Gambia is consolidating its democratic change by successfully organizing peaceful and transparent elections. President Barrow was reelected for a second five-year term in December 2021; his party and its alliance hold half of the parliamentary seats following an election in April 2022. A fourth wave of the COVID-19 pandemic hit the country in late 2021-early 2022. New infection cases have dropped to almost nil recently. The vaccination rate currently stands at about 20 percent of the adult population. The Gambia is already facing significant repercussions of the war in Ukraine.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Gambia, The